Potential for quantifying general environmental resilience of dairy cattle in sub-Saharan Africa using deviations in milk yield - Oloo, Richard Dooso; Mrode, Raphael A.; Bennewitz, Jörn; Ekine-Dzivenu, Chinyere C.; Ojango, Julie M.K.; Gebreyohanes, Gebregziabher; Okeyo Mwai, Ally; Chagunda, Mizeck G.G. (Frontiers Media, 2023)
Introduction: Genetic improvement of general resilience of dairy cattle is deemed as a part of the solution to low dairy productivity and poor cattle adaptability in sub-Saharan Africa (SSA). While indicators of general resilience have been proposed and evaluated in other regions, their applicability in SSA remains unexplored. This study sought to test the viability of utilizing log-transformed variance (LnVar), autocorrelation (rauto), and skewness (Skew) of deviations in milk yield as indicators of general resilience of dairy cows performing in the tropical environment of Kenya.